2020
DOI: 10.1371/journal.pone.0227542
|View full text |Cite
|
Sign up to set email alerts
|

Community’s perception, experiences and health seeking behavior towards newborn illnesses in Debre Libanos District, North Shoa, Oromia, Ethiopia: Qualitative study

Abstract: Background Worldwide about 4 million newborns die each year; of which around 600,000 newborns die from series bacterial infections. To reduce newborn death, community based newborn care is being implemented in Ethiopia though its utilization by clients is low. Studies conducted to address perception of the community towards newborn illnesses are limited. Therefore, this study was aimed in exploring community member's perception, experiences and health seeking behavior towards newborn illnesses. Methods A descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…This local illness diagnosis makes the community members perceive that newborn illnesses have no medical treatment from health facilities, and rely on the traditional medicines rather than seeking care from health facilities; developing misconception on treatment options. These findings are consistent with the findings of studies conducted in central and southern Ethiopia, Nigeria, and Bangladesh in that community members use herbal medicine to treat newborn illnesses [23][24][25][26][27][28]. This study also found that community members perceive newborn illnesses as non-severe which resolve spontaneously within a few days.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This local illness diagnosis makes the community members perceive that newborn illnesses have no medical treatment from health facilities, and rely on the traditional medicines rather than seeking care from health facilities; developing misconception on treatment options. These findings are consistent with the findings of studies conducted in central and southern Ethiopia, Nigeria, and Bangladesh in that community members use herbal medicine to treat newborn illnesses [23][24][25][26][27][28]. This study also found that community members perceive newborn illnesses as non-severe which resolve spontaneously within a few days.…”
Section: Discussionsupporting
confidence: 91%
“…This study also found that community members perceive newborn illnesses as non-severe which resolve spontaneously within a few days. This finding is consistent with findings from different studies conducted at different settings in that community members in those settings delay sought health care from health facilities due to expectation of self-resolution [28,29] and considering the symptoms as minor that resolve within next few days [28,30]. This calls a need to conduct a behavioral change communication to change the behavior of the community members towards newborn illnesses and their treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Erroneous beliefs about causes of illnesses in SYIs such as linking illnesses to a child's given name were also common. Our findings are similar to studies conducted elsewhere in low-and middle-income countries where illnesses or death to children have been attributed to PLOS ONE the 'evil eye' or malevolent spirits [7,10,[29][30][31]. A study in the Ashanti Region of Ghana revealed how caregivers attributed pregnancy loss and newborn mortality to a local illness called asram-believed to be caused by evil spirits [11].…”
Section: Discussionsupporting
confidence: 87%
“…A similar finding have been noted in qualitative studies conducted in Ghana and Nigeria [25,26]. While illness conceptualization play an important role in the decision regarding treatment options [27,28], knowledge of biomedical causes alone may not lead to healthcare-seeking from facilities in settings where traditional beliefs are pervasive [29,30]. There is need for interventions to reinforce correct beliefs about causation and treatment of illnesses in SYIs to promote care-seeking from health facilities.…”
Section: Discussionsupporting
confidence: 72%